2007
DOI: 10.1007/978-3-540-76778-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Resource-Intensive Applications Made Easy

Abstract: Abstract. Snowbird is a middleware system based on virtual machine (VM) technology that simplifies the development and deployment of bimodal applications. Such applications alternate between phases with heavy computationalresource needs and phases rich in user interaction. Examples include digital animation, as well as scientific, medical, and engineering diagnostic and design tools. Traditionally, these applications have been manually partitioned into distributed components to take advantage of remote computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The latency issue is very crucial in mobile cloud application models [107]. Therefore, the proposed model offloads the computation to the nearby infrastructure instead of distant clouds to avoid delays incurred by wide-area networks.…”
Section: ) Satyanarayanan Et Al Model: In [2] Satyanarayanan Et Almentioning
confidence: 99%
“…The latency issue is very crucial in mobile cloud application models [107]. Therefore, the proposed model offloads the computation to the nearby infrastructure instead of distant clouds to avoid delays incurred by wide-area networks.…”
Section: ) Satyanarayanan Et Al Model: In [2] Satyanarayanan Et Almentioning
confidence: 99%
“…Humans are acutely sensitive to delay and jitter, and it is very difficult to control these parameters at WAN scale. The work by Lagar-Cavilla et al [13] has shown that latency can negatively impact interactive response even when bandwidth is adequate. Networks with high delay-bandwidth products are therefore disastrous for remote execution of interactive applications; in contrast, local execution on a Transient PC does not suffer from this problem.…”
Section: Fully Exploiting Local Hardware Resources In Transient Pcsmentioning
confidence: 99%
“…Further, encryption and other mechanisms that may be added to secure transmissions must not add a significant overhead to the latency. [13], [14] discuss the effect of latency on user experience, specifically users of thin clients.…”
Section: B Migration To Pervasive Systemsmentioning
confidence: 99%